Sunni communities in the Islamic Republic of Iran, 2013-2021: securitization, secularization and privatization - Habibi Doroh, Hessam (Social, economic and political studies of the Middle East and Asia, 2023)
"Sunni-Shia relations in Iran offer an analytical guide for the interpretation of inequality, securitization, and immigration. This book reorients our understanding of contemporary Iran by answering still unacknowledged questions: how is the relationship, the interaction and socio-political behaviour between the Islamic Republic and its Sunni minorities? Using unexamined sources and fieldwork, Hessam Habibi Doroh shows a clear insight into the life of Iranian Sunnis, their contention and cooperation with the state during Hasan Rouhani's presidency. Comparison with the wider region complements this nuanced portrayal of impacts of privatization, secularization, and securitization on the sectarian relations between the state and its minorities"--